ETNOMATEMATIKA DALAM ANYAMAN TIKAR PADA MASYARAT PADANG TIKAR - Adelia, Risma; Sarassanti, Yumi (Tadris Matematika, 2025)
The purpose of this study is to find out the mathematical concept and obtain information on mat weaving in Padang Tikar village. The type of research used is qualitative descriptive research with an ethnographic approach. Data obtained from this study through observation, interviews and documentation. The subjects of this study involved 4 subjects, namely 3 mat weaving craftsmen in Padang Tikar Village and 1 elder who knows the history of mat weaving culture in Padang Tikar Village. The results of this study so that we can find out the mathematical concepts that exist in mat weaving, the mathematical concepts that exist in mat weaving are geometric concepts, namely lines, perpendicular lines, flat shapes (squares, triangles,) and spatial shapes (cylinders).